Coating-free laser shock peening method for improving mechanical property of AISI9310 gear steel material
Through the uncoated laser impact enhancement technology, the water-optical coaxial laser beam is used to directly perform laser impact on the surface of the AISI9310 gear steel material, which solves the problem of unsatisfactory strengthening effect of gear components in the traditional method, achieves the improvement of microhardness and residual compressive stress, and improves the mechanical properties and surface characteristics of the gear.
Patent Information
- Application Number
- CN202411842938.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional laser impact enhancement processes are difficult to achieve ideal strengthening effects in gear components, especially at the root of the tooth, where spot distortion and unsatisfactory strengthening effects are present.
The uncoated laser impact enhancement method is adopted, and the water-optical coaxial laser beam design is used to directly strengthen the laser impact enhancement on the surface of the AISI9310 gear steel material sample, avoiding the use of the absorption protective layer, and using small-size spots and low-energy laser beams to ensure effective strengthening.
It effectively improves the mechanical properties of AISI9310 gear steel material, improves microhardness and introduces high amplitude residual compressive stress, forms a gradient hardening layer and stress layer, and improves the wear resistance and surface integrity of the gear.
Smart Images

Figure CN119571048A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser shock intensive processing, and in particular to a coating-free laser shock intensive processing method for improving the mechanical properties of AISI9310 gear steel material. Background Art
[0002] Laser shock peening is a non-contact strengthening process that uses laser-induced shock waves to achieve surface modification. It introduces high-amplitude residual compressive stress and gradient nanocrystalline structure to achieve a unique work hardening effect. The laser energy during traditional laser shock peening is at the Joule level. In order to ensure the consistency of the strengthening and modification layer, it is necessary to evenly cover the surface of the sample to be strengthened with an absorption protective layer, such as Figure 1 As shown. However, gear failures made of martensitic AISI9310 gear steel materials usually occur at the root of the tooth below the pitch circle. Irregular geometric dimensions make it difficult to set a flat constraint layer and protective layer. In addition, the millimeter-scale spot is easily distorted at the root of the tooth, which greatly weakens the strengthening effect and fails to achieve the ideal strengthening effect.
[0003] In view of this, it is necessary to improve the original laser shock peening process to meet such special strengthening requirements. Summary of the invention
[0004] Aiming at improving the reliable working margin and full-cycle life of gear components, the present invention provides a coating-free laser shock strengthening method for improving the mechanical properties of the martensitic AISI9310 gear steel material after carburizing heat treatment.
[0005] The technical solution provided by the present invention is as follows:
[0006] The present invention provides a coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material comprises the following steps:
[0007] Obtain AISI9310 gear steel material specimens to be strengthened;
[0008] The AISI9310 gear steel material sample to be strengthened is pretreated, and then fixed in the laser loading platform fixture, and the distance between the light source laser beam, the galvanometer and the sample is adjusted to ensure that the laser spot is focused on the position to be strengthened;
[0009] Turn on the water source switch of the water-optical coaxial laser to establish a water confinement layer on the surface of the AISI9310 gear steel material sample to be strengthened;
[0010] The strengthened AISI9310 gear steel material samples were post-processed.
[0011] Furthermore, the step of pretreating the AISI9310 gear steel material sample to be strengthened includes the following process:
[0012] The AISI9310 gear steel material sample to be strengthened is placed in anhydrous ethanol medium for a first ultrasonic cleaning, then polished in a polishing machine using SiO2 solution and placed in anhydrous ethanol medium again for a first ultrasonic cleaning.
[0013] Furthermore, the working condition parameters of the ultrasonic cleaning include: time>5 minutes, ultrasonic power of 800-900W.
[0014] Furthermore, when the water source switch of the water-optical coaxial laser is turned on to establish a water confinement layer on the surface of the AISI9310 gear steel material sample to be strengthened, the laser process parameters are set in the program control software to perform laser shock strengthening twice, with an interval of 1 minute between the two strengthenings.
[0015] Furthermore, the laser process parameters are as follows: overlap rate 50%, pulse width 15ns, circular spot diameter 0.8mm, Gaussian energy distribution light source, frequency 59Hz, wavelength 532nm.
[0016] Furthermore, the step of post-processing the strengthened AISI9310 gear steel material sample includes the following processes:
[0017] The strengthened AISI9310 gear steel material sample was taken out from the laser platform fixture, and placed in flowing dry hot air until the surface moisture was completely evaporated, and then added into anhydrous ethanol medium for a second ultrasonic cleaning.
[0018] Furthermore, the working condition parameters of the second ultrasonic cleaning include: time of 3 to 5 minutes, ultrasonic power of 750 to 850W.
[0019] Furthermore, the coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material also includes:
[0020] The post-treated AISI9310 gear steel material samples were placed under an optical microscope for observation, and the metallographic structure of the strengthened AISI9310 gear steel material samples and the surface periodic microstructure morphology caused by ablation were analyzed;
[0021] The AISI9310 gear steel material sample after strengthening was cut in the middle by wire cutting, and the mechanical properties of the cut section were evaluated by microhardness tester and residual stress tester along the laser incident direction.
[0022] Furthermore, the energy of the uncoated laser shock peening is at the mJ level, the diameter of the laser spot is at the μm level, and the depth of the shock wave action layer is less than 0.5 mm.
[0023] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0024] In the traditional laser shock peening technology, the present invention innovatively adopts the water-light coaxial laser beam design, does not set an absorption protection layer during the strengthening process, and adopts a coating-free laser shock peening method, which effectively improves the mechanical properties of AISI9310 gear steel materials and makes up for the shortcomings of the existing technology. Specifically:
[0025] 1) In the traditional laser shock strengthening technology, the present invention innovatively adopts a water-light coaxial laser beam design, does not set an absorption protection layer during the strengthening process, and uses a smaller size of strengthening spot and laser energy to ensure that the laser power density is within the effective strengthening parameter range. During the coating-free laser shock strengthening, the laser beam and the target material directly interact to form a self-lubricating periodic microstructure pattern, the plasma expansion induced by the laser bombardment of the gear sample surface, the shock wave propagates inside the material to cause plastic deformation, the gradient grain refinement and the dislocation density are greatly increased, thereby effectively improving the mechanical properties.
[0026] 2) In the traditional laser shock strengthening technology, the laser shock strengthening energy is greater than 2J, the spot diameter is greater than 2mm, and the depth of the shock wave action layer is greater than 1.2mm. In order to ensure the consistency of the strengthening and modification layer, it is necessary to evenly cover the surface of the sample to be strengthened with an absorption protective layer, and there is a reflected shock wave. The strengthening effect on the gears obtained from martensitic AISI9310 gear steel materials is not ideal; while the energy of the coating-free laser shock strengthening in the present invention is mJ level, the diameter of the laser spot is μm level, and the depth of the shock wave action layer is less than 0.5mm, which can meet the special strengthening requirements of gears obtained from martensitic AISI9310 gear steel materials; at the same time, water-light coaxial laser shock strengthening equipment is used, and the processing efficiency is 40cm 2 / min, processing accuracy 5μm / 5", single pulse laser energy <150mJ, beam quality M2≤1.25, surface modification of gear steel materials is implemented in an integrated laser shock peening platform system.
[0027] 3) Laser parameters are the key influencing factors when laser shock peening is performed without coating. To avoid ablation, a laser beam with a lower power density must be used for modification. Preliminary tests have verified that a small spot size (<1mm) keeps the single pulse laser power density at 5-10GW / cm 2, the shock wave pressure can still reach the Hugoniot elastic limit and introduce an effective work hardening layer. Ensure that the laser shock strengthening of gear parts can be implemented efficiently and stably, solve the technical defects of laser shock strengthening in the application scenarios of gears, and improve economic production benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0030] Figure 1 Schematic diagram of the principle of laser shock strengthening for improving the mechanical properties of AISI9310 gear steel material.
[0031] Figure 2 A schematic diagram of the principle of the coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material provided by the present invention.
[0032] Figure 3 The present invention provides a flow chart of a coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material.
[0033] Figure 4 A comparison diagram of the hardness distribution in the depth direction of an AISI9310 gear steel material sample after uncoated laser shock strengthening to improve the mechanical properties of the AISI9310 gear steel material provided by the present invention and an unstrengthened AISI9310 gear steel material.
[0034] Figure 5 A comparison diagram of the residual compressive stress distribution in the depth direction of the AISI9310 gear steel material sample after uncoated laser shock strengthening to improve the mechanical properties of the AISI9310 gear steel material provided by the present invention and the unstrengthened AISI9310 gear steel material.
[0035] Figure 6 The present invention provides a periodic micro-protrusion structure morphology of an AISI9310 gear steel material sample after uncoated laser shock strengthening to improve the mechanical properties of the AISI9310 gear steel material.
[0036] Figure 7The hardness distribution diagram of the AISI9310 gear steel material sample in the depth direction after laser shock strengthening to improve the mechanical properties of the AISI9310 gear steel material.
[0037] Figure 8 This is the residual compressive stress diagram of the AISI9310 gear steel material sample in the depth direction after laser shock strengthening to improve the mechanical properties of the AISI9310 gear steel material. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0040] The present invention provides a coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material. Figure 3 As shown, the coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material includes the following steps:
[0041] Obtain AISI9310 gear steel material specimens to be strengthened;
[0042] The AISI9310 gear steel material sample to be strengthened is pretreated, and then fixed in the laser loading platform fixture, and the distance between the light source laser beam, the galvanometer and the sample is adjusted to ensure that the laser spot is focused on the position to be strengthened;
[0043] Turn on the water source switch of the water-optical coaxial laser to establish a water confinement layer on the surface of the AISI9310 gear steel material sample to be strengthened;
[0044] The strengthened AISI9310 gear steel material samples were post-processed.
[0045] In terms of the technical methods of traditional laser shock peening, the present invention innovatively adopts a water-light coaxial laser beam design, does not set an absorption protective layer during the strengthening process, and adopts a coating-free laser shock peening method, which effectively improves the mechanical properties of AISI9310 gear steel material and makes up for the shortcomings of the existing technology.
[0046] In some specific embodiments, the AISI9310 gear steel material sample to be strengthened can directly adopt the commercially available AISI9310 gear steel material that can meet the actual use requirements; or it can be homemade according to the existing AISI9310 gear steel material preparation process, such as cutting the AISI9310 gear steel rod-shaped mother material into blocks of 1cm×1cm×5mm, and sequentially performing high-temperature tempering, quenching and other heat treatments and carburizing processes to ensure that the sample reaches the actual performance state of the gear.
[0047] In some specific embodiments, the step of pretreating the AISI9310 gear steel material sample to be strengthened comprises the following process:
[0048] The AISI9310 gear steel material sample to be strengthened is placed in anhydrous ethanol medium for a first ultrasonic cleaning, then polished in a polishing machine using SiO2 solution and placed in anhydrous ethanol medium again for a first ultrasonic cleaning.
[0049] In some specific embodiments, the working condition parameters of the ultrasonic cleaning include: time>5 minutes, ultrasonic power of 800-900W.
[0050] In some specific embodiments, when the water source switch of the water-optic coaxial laser is turned on to establish a water confinement layer on the surface of the AISI9310 gear steel material sample to be strengthened, the laser process parameters are set in the program control software to perform laser shock strengthening twice, with an interval of 1 minute between the two strengthenings.
[0051] In some specific embodiments, the laser process parameters are: overlap rate 50%, pulse width 15ns, circular spot diameter 0.8mm, Gaussian energy distribution light source, frequency 59Hz, wavelength 532nm.
[0052] In some specific embodiments, the step of post-processing the strengthened AISI9310 gear steel material sample comprises the following process:
[0053] The strengthened AISI9310 gear steel material sample was taken out from the laser platform fixture, and placed in flowing dry hot air until the surface moisture was completely evaporated, and then added into anhydrous ethanol medium for a second ultrasonic cleaning.
[0054] In some specific embodiments, the working condition parameters of the second ultrasonic cleaning include: time of 3 to 5 minutes, ultrasonic power of 750 to 800W.
[0055] In some specific embodiments, the coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material further includes:
[0056] The post-treated AISI9310 gear steel material samples were placed under an optical microscope for observation, and the metallographic structure of the strengthened AISI9310 gear steel material samples and the surface periodic microstructure morphology caused by ablation were analyzed;
[0057] The AISI9310 gear steel material sample after strengthening was cut in the middle by wire cutting, and the mechanical properties of the cut section were evaluated by microhardness tester and residual stress tester along the laser incident direction.
[0058] In some specific embodiments, the energy of the uncoated laser shock peening is at the mJ level, the diameter of the laser spot is at the μm level, and the depth of the shock wave action layer is less than 0.5 mm.
[0059] It should be noted that the raw materials involved in the coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material provided by the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade according to the preparation process disclosed in the prior art; at the same time, the operating steps and condition parameters involved, unless otherwise specified or specified, can be carried out according to existing processes or using existing equipment, and the present invention document will not describe them one by one.
[0060] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0061] Example
[0062] This example provides a coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material. The object of the coating-free laser shock strengthening is a block sample of AISI9310 gear steel. In order to simulate the working condition of the real gear, the heat treatment process is carried out in accordance with relevant standards. Considering the size effect of laser shock strengthening, the sample size is designed to be 1cm×1cm×5mm, of which the thickness of the carburized layer is about 1mm, the thickness of the complete carburized layer is about 480μm, and the carburized layer completely covers the depth of the coating-free laser shock strengthening. Strengthening is carried out without setting an absorption protective layer. The water-light coaxial water constraint layer design is adopted to carry out overlapping strengthening of the pulsed laser beam. After a complete strengthening along the X-axis direction, the strengthening of the next area is carried out to ensure the uniformity of the modification. The laser path of the laser beam is set to a Z-shaped shape to facilitate the efficient rotation processing mode. The specific parameters used for coating-free laser shock strengthening are as follows: the pulsed laser energy is 120mJ, the spot overlap rate is 50%, and the pulse width is 15ns. In order to ensure the coherent spot overlap, the spot is selected as a standard circular spot with a diameter of 0.8 mm, a frequency of 65 Hz, and a Gaussian energy distribution of the laser beam light source.
[0063] The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material comprises the following steps:
[0064] S1: Obtain the AISI9310 gear steel material sample to be strengthened, with a size of 1cm×1cm×5mm; specifically: cut the AISI9310 gear steel rod-shaped base material into a block sample of 1cm×1cm×5mm, perform two vacuum carburizing processes, and perform strong carburizing at 930℃ for 5 hours and then cool it, with a carbon potential of 1.3%. Then perform strong carburizing at 930℃ for 7 hours and then cool it and temper it at high temperature in a salt furnace, quench it at 800℃ and temper it at 180℃ to eliminate the residual stress during the quenching process, and finally slowly cool it to room temperature. The measured surface hardness is HRC60, the fully carburized layer is 480μm, and the transition carburized layer is 520μm. The metallographic structures of the sample from the surface to the core are needle-shaped martensite and lath-shaped martensite, respectively, and there is a small amount of residual austenite remaining from the heat treatment. The heat-treated sample truly restores the mechanical properties of high hardness on the outside and high toughness in the core of the aviation gear;
[0065] S2: The AISI9310 gear steel material sample to be strengthened obtained in S1 was ultrasonically cleaned in anhydrous ethanol medium for 10 minutes, with an ultrasonic power of 900W; then polished in a polishing machine with SiO2 solution until the surface roughness dropped below 0.08μm, and ultrasonic cleaning was repeated to remove polishing debris; ultrasonic cleaning was repeated. Then the platform angle was adjusted to horizontal, the sample was fixed in the laser stage fixture, and the distance between the light source laser beam, the galvanometer and the sample was adjusted to ensure that the laser spot was focused on the position to be strengthened.
[0066] S3: Turn on the water source switch of the water-optical coaxial laser to ensure that the flowing water constraint layer covers the surface of the sample of S2, and then perform uncoated laser shock strengthening in a normal temperature atmospheric environment. After the laser parameter process is optimized through preliminary tests, the pulse laser energy is set to 120mJ, the spot overlap rate is 50%, and the pulse width is 15ns through laser program control; the spot is selected to be a circular spot with a diameter of 0.8mm and a frequency of 65Hz. The laser beam light source has a Gaussian energy distribution. The beam is scanned twice repeatedly, and the interval between the two laser shock strengthenings is 1 minute to eliminate the heat accumulation of the laser on the surface of the material. The scanning path is set to Z-shaped rotary processing. After a complete strengthening along the X-axis direction, it moves down along the Y-axis direction to strengthen the next area until all areas to be strengthened are covered;
[0067] S4: The strengthened AISI9310 gear steel material sample obtained in S3 is taken out from the fixture, and is placed in flowing dry hot air until the surface moisture is completely evaporated, and then ultrasonically cleaned in anhydrous ethanol medium for 5 minutes with an ultrasonic power of 900W;
[0068] S5: The strengthened AISI9310 gear steel material obtained in S4 was observed under an optical microscope to analyze the metallographic structure after strengthening and the surface periodic microstructure morphology caused by ablation;
[0069] S6: The sample obtained in S5 is cut in the middle by wire cutting, and the mechanical properties of the cut section are evaluated by microhardness tester and residual stress tester along the laser incident direction, with a test range of 1000μm, to determine the strengthening effect.
[0070] Figure 4 The present invention provides a comparison diagram of the hardness distribution in the depth direction of the AISI9310 gear steel material sample after uncoated laser shock strengthening and the unstrengthened AISI9310 gear steel material to improve the mechanical properties of the AISI9310 gear steel material. The horizontal axis represents the test position in the depth direction, and the vertical axis represents the hardness value in Hv. In order to avoid contingency, three points are taken at the same depth each time to test the microhardness, and finally the hardness distribution curves of the uncoated laser shock strengthened and unstrengthened samples along the depth direction are obtained. Figure 4 It can be seen that after the uncoated laser shock strengthening, the hardness and residual stress of the sample in the XZ cross-sectional direction were measured, and it was found that the microhardness in the cross-sectional depth direction was significantly improved after strengthening, and a high-amplitude residual compressive stress field was introduced. The thickness of the work-hardened layer caused by the shock wave is about 460μm. Within the effective hardening range, the microhardness of the untreated sample increased from 625Hv to 670.9Hv, an increase of about 7.3%.
[0071] Figure 5The present invention provides a comparison diagram of the residual compressive stress distribution in the depth direction of the AISI9310 gear steel material sample after uncoated laser shock strengthening and the unstrengthened AISI9310 gear steel material to improve the mechanical properties of the AISI9310 gear steel material. Three points are taken at the same depth to test the residual stress value, and finally the residual stress distribution curves of the uncoated laser shock strengthened and unstrengthened samples along the depth direction are obtained. Figure 5 It can be seen that a high-amplitude residual compressive stress field is introduced into the sample and gradually decays along the depth direction. The thickness of the residual compressive stress layer is about 385μm. The maximum residual compressive stress of 748.9MPa is introduced at a depth of 210μm.
[0072] Figure 6 The periodic micro-protrusion structure morphology of the AISI9310 gear steel material sample after the uncoated laser shock strengthening for improving the mechanical properties of the AISI9310 gear steel material provided by the present invention is shown in FIG. Figure 6 It can be seen that due to the limitation of the spot shape and size, the surface is covered with a regular arrangement of rectangular micro-protrusion structure patterns, and the size of a single micro-protrusion is 220-250μm. Uncoated laser shock strengthening prepares a regular morphological feature pattern with self-lubricating functionality, which is beneficial to improve the surface integrity and wear resistance of the gear. The 120mJ laser energy used limits the thermal effect during uncoated strengthening. The 0.8mm spot size makes the laser power density greater than 5GW / cm 2 , the maximum peak pressure of the shock wave can still reach the Hugoniot elastic limit and introduce effective plastic deformation and residual compressive stress field. When applied to components with complex geometric shapes such as gears, the smaller spot size of LSPwc can avoid the distortion of the spot shape at the root of the tooth, and the smaller energy is not easy to cause processing damage such as ablation. In the strengthening domain around the root of the tooth, which is prone to fatigue cracks, the plastic deformation layer introduced by the shock wave along the laser incident direction is the fundamental reason for the gradient refinement of grains and the increase in dislocation density, which manifests as a gradient hardening layer and a stress layer. In addition, the finer grain layer on the surface can effectively avoid problems such as stress relaxation caused by mechanical heat when the gears are meshed after strengthening. The improvement of the comprehensive mechanical properties and the periodic microstructure pattern on the surface ensure the effectiveness of coating-free laser shock strengthening in gear components.
[0073] Comparative Example
[0074] This example provides a method for laser shock strengthening of an existing AISI9310 gear steel material to improve its mechanical properties, comprising the following steps:
[0075] The object of laser shock strengthening is AISI9310 gear steel block specimen. In order to simulate the working condition of the real gear, the heat treatment process is carried out in accordance with relevant standards. The specimen size is designed to be 1cm×1cm×5mm, of which the thickness of the carburized layer is about 1mm and the thickness of the fully carburized layer is about 480μm. An aluminum foil absorption protection layer and a water constraint layer are set in the strengthening process. The overlapping strengthening of the pulsed laser beam is carried out. After a complete strengthening along the X-axis direction, the strengthening of the next area is carried out to ensure the uniformity of the modification. The laser path of the laser beam is set to a Z-shaped shape to facilitate the efficient rotation processing mode. The specific parameters used in laser shock strengthening are as follows: the pulsed laser energy is 120mJ, the spot overlap rate is 50%, and the pulse width is 15ns. In order to ensure the coherent spot overlap, the spot selects a standard circular spot with a diameter of 0.8mm, a frequency of 65Hz, and a Gaussian energy distribution for the laser beam light source.
[0076] The laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material comprises the following steps:
[0077] S1: Obtain the AISI9310 gear steel material sample to be strengthened, with a size of 1cm×1cm×5mm; specifically: cut the AISI9310 gear steel rod-shaped base material into a block sample of 1cm×1cm×5mm, perform two vacuum carburizing processes, and perform strong carburizing at 930℃ for 5 hours and then cool it, with a carbon potential of 1.3%. Then perform strong carburizing at 930℃ for 7 hours and then cool it and temper it at high temperature in a salt furnace, quench it at 800℃ and temper it at 180℃ to eliminate the residual stress during the quenching process, and finally slowly cool it to room temperature. The measured surface hardness is HRC60, the fully carburized layer is 480μm, and the transition carburized layer is 520μm. The metallographic structures of the sample from the surface to the core are needle-shaped martensite and lath-shaped martensite, respectively, and there is a small amount of residual austenite remaining from the heat treatment. The heat-treated sample truly restores the mechanical properties of high hardness on the outside and high toughness in the core of the aviation gear;
[0078] S2: The AISI9310 gear steel material sample to be strengthened obtained in S1 was ultrasonically cleaned in anhydrous ethanol medium for 10 minutes, with an ultrasonic power of 900W; then polished in a polishing machine with SiO2 solution until the surface roughness dropped below 0.08μm, and ultrasonic cleaning was repeated to remove polishing debris; ultrasonic cleaning was repeated. Then the platform angle was adjusted to horizontal, the sample was fixed in the laser stage fixture, and the distance between the light source laser beam, the galvanometer and the sample was adjusted to ensure that the laser spot was focused on the position to be strengthened.
[0079] S3: Turn on the water source switch to ensure that the water constraint layer covers the surface of the sample in S2, and cover the surface of the sample with an aluminum foil layer with a thickness not exceeding 100μm. Then, laser shock strengthening is carried out in a normal temperature atmospheric environment. After the laser parameter process is optimized through preliminary tests, the pulse laser energy is set to 120mJ, the spot overlap rate is 50%, and the pulse width is 15ns through laser program control; the spot selects a circular spot with a diameter of 0.8mm and a frequency of 65Hz. The laser beam light source has a Gaussian energy distribution. The beam is scanned twice repeatedly, with an interval of 1 minute between the two laser shock strengthenings to eliminate the heat accumulation of the laser on the surface of the material. The scanning path is set to Z-shaped rotary processing. After a complete strengthening along the X-axis direction, it moves down along the Y-axis direction to strengthen the next area until all areas to be strengthened are covered;
[0080] S4: The strengthened AISI9310 gear steel material sample obtained in S3 is taken out from the fixture, and is placed in flowing dry hot air until the surface moisture is completely evaporated, and then ultrasonically cleaned in anhydrous ethanol medium for 5 minutes with an ultrasonic power of 900W;
[0081] S5: The sample obtained in S4 is cut in the middle by wire cutting, and the mechanical properties of the cut section are evaluated by microhardness tester and residual stress tester along the laser incident direction, with a test range of 1000μm, to determine the strengthening effect. Figure 7 The hardness distribution diagram of AISI9310 gear steel material sample in the depth direction after laser shock strengthening is used to improve the mechanical properties of AISI9310 gear steel material. Figure 7 and Figure 4 By comparison, when the laser parameters of uncoated laser shock peening are used for traditional coated laser shock peening, the absorbing protective layer dissipates part of the plasma shock wave energy, and the attenuation of the shock wave force effect leads to the failure to effectively introduce the work hardening effect.
[0082] Figure 8 The residual compressive stress diagram of AISI9310 gear steel material sample in the depth direction after laser shock strengthening is used to improve the mechanical properties of AISI9310 gear steel material. Figure 8 and Figure 5 By comparison, it can be seen that when the laser parameters of uncoated laser shock peening are used for traditional coated laser shock peening, the absorbing protective layer dissipates a part of the plasma shock wave energy, the shock wave quickly decays below the Hugoniot elastic limit, and the reduction in the degree of plastic deformation leads to a significant reduction in the amplitude and impact depth of the beneficial residual compressive stress.
[0083] In summary, the coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel provided by the patent of this invention improves the laser shock strengthening technology of gear steel. It solves the technical defect that the traditional coated laser shock strengthening is not suitable for gear parts, and has the advantages of improving mechanical properties and surface integrity. The operation process is efficient and convenient, and has the characteristics of high industrial application value and industrial applicability.
[0084] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0085] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material, characterized in that: The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material comprises the following steps: Obtain AISI9310 gear steel material specimens to be strengthened; The AISI9310 gear steel material sample to be strengthened is pretreated, and then fixed in the laser loading platform fixture, and the distance between the light source laser beam, the galvanometer and the sample is adjusted to ensure that the laser spot is focused on the position to be strengthened; Turn on the water source switch of the water-optical coaxial laser to establish a water confinement layer on the surface of the AISI9310 gear steel material sample to be strengthened; The strengthened AISI9310 gear steel material samples were post-processed.
2. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 1 is characterized in that: The step of pre-treating the AISI9310 gear steel material sample to be strengthened The process includes: The AISI9310 gear steel material sample to be strengthened is placed in anhydrous ethanol medium for a first ultrasonic cleaning, then polished in a polishing machine using SiO2 solution and placed in anhydrous ethanol medium again for a first ultrasonic cleaning.
3. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 2 is characterized in that: The working condition parameters of the ultrasonic cleaning include: time>5 minutes, ultrasonic power of 800-900W.
4. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 1 is characterized in that: When the water source switch of the water-optical coaxial laser is turned on to establish a water confinement layer on the surface of the AISI9310 gear steel material sample to be strengthened, the laser process parameters are set in the program control software to perform laser shock strengthening twice, with an interval of 1 minute between the two strengthenings.
5. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 1, characterized in that: The laser process parameters are as follows: overlap rate 50%, pulse width 15ns, circular spot diameter 0.8mm, Gaussian energy distribution light source, frequency 59Hz, wavelength 532nm.
6. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 1 is characterized in that: The steps of post-processing the strengthened AISI9310 gear steel material specimen include the following processes: The strengthened AISI9310 gear steel material sample was taken out from the laser platform fixture, and placed in flowing dry hot air until the surface moisture was completely evaporated, and then added into anhydrous ethanol medium for a second ultrasonic cleaning.
7. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 6 is characterized in that: The working condition parameters of the second ultrasonic cleaning include: time of 3 to 5 minutes, ultrasonic power of 750 to 850W.
8. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 1, characterized in that: The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material also includes: The post-treated AISI9310 gear steel material samples were placed under an optical microscope for observation, and the metallographic structure of the strengthened AISI9310 gear steel material samples and the surface periodic microstructure morphology caused by ablation were analyzed; The AISI9310 gear steel material sample after strengthening was cut in the middle by wire cutting, and the mechanical properties of the cut section were evaluated by microhardness tester and residual stress tester along the laser incident direction.
9. The coating-free laser shock strengthening method for improving the mechanical properties of AISI9310 gear steel material according to claim 1, characterized in that: The energy of uncoated laser shock peening is at the mJ level, the diameter of the laser spot is at the μm level, and the depth of the shock wave action layer is less than 0.5mm.
Citation Information
Cited By
Die steel surface strengthening treatment method and system based on laser hardening
CN121380507A